Selma to Saigon : the civil rights movement and the Vietnam War - Lucks, Daniel S., 1962- (Civil rights and the struggle for Black equality in the twentieth century., 2014)
The civil rights and anti--Vietnam War movements were the two greatest protests of twentieth-century America. The dramatic escalation of U.S. involvement in Vietnam in 1965 took precedence over civil rights legislation, which had dominated White House and congressional attention during the first half of the decade. The two issues became intertwined on January 6, 1966, when the Student Nonviolent Coordinating Committee (SNCC) became the first civil rights organization to formally oppose the war, protesting the injustice of drafting African Americans to fight for the freedom of the South Vietnam.